The proteome of human brain microdialysate - Maurer, Martin H.; Berger, Christian; Wolf, Margit; Fütterer, Carsten Dietmar; Feldmann, Robert Enrico; Schwab, Stefan; Kuschinsky, Wolfgang (Proteome science, 2003)
Cerebral microdialysis has been established as a monitoring tool in neurocritically ill patients suffering from severe stroke. The technique allows to sample small molecules in the brain tissue for subsequent biochemical analysis. In this study, we investigated the proteomic profile of human cerebral microdialysate and if the identified proteins might be useful predictors for disease characteristics in stroke for tissue at risk in the contralateral hemisphere. We analysed cerebral protein expression in microdialysate from three stroke patients sampled from the hemisphere contralateral to the lesion. Using a proteomic approach based on two-dimensional gel electrophoresis and subsequent mass spectrometry, we created a protein map for the global protein expression pattern of human microdialyste.